2015
DOI: 10.1007/s11224-015-0720-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds in quinoline N-oxide derivatives: first-principle molecular dynamics and metadynamics ground state study

Abstract: Car-Parrinello molecular dynamics simulations were carried out for 8-hydroxyquinoline N-oxide (1) and 2-carboxyquinoline N-oxide (2) in vacuo and in the solid state. The first-principle approach was employed to intramolecular hydrogen bond features present in the studied quinoline N-oxides. Grimme's dispersion correction was employed throughout the study. Special attention was devoted to the solid-state computations knowing that in the molecular crystals, strong and weak interactions are responsible for spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…They assigned a feature at 2330 cm −1 to the OH stretching band, but the P(Harm) value is 2877 cm −1 [ 19 ]. The P(Harm) prediction was confirmed by correlation with NMR parameters [ 19 ] and was subsequently supported by the results of an advanced molecular dynamics simulation [ 70 ].…”
Section: Theoretical Predictionsmentioning
confidence: 80%
See 1 more Smart Citation
“…They assigned a feature at 2330 cm −1 to the OH stretching band, but the P(Harm) value is 2877 cm −1 [ 19 ]. The P(Harm) prediction was confirmed by correlation with NMR parameters [ 19 ] and was subsequently supported by the results of an advanced molecular dynamics simulation [ 70 ].…”
Section: Theoretical Predictionsmentioning
confidence: 80%
“…In an analysis of the importance of vibrationally enhanced catalysis, Kamerlin, Mavri, and Warshel [ 66 ] concluded that dynamical effects and tunneling are irrelevant for enzyme catalysis. Car-Parrinello molecular dynamics calculations were also applied by Durlak et al [ 67 , 68 , 69 ] in investigations of the vibrational structure of compounds like nitromalonamide enol ( 4 ) and 2-acetyl-1,8-dihydroxy-3,6-dimethylnaphthalene ( 7 ), and by Panek et al [ 70 ] in a study of intramolecular hydrogen bonds in a series of 8-hydroxyquinoline N -oxide ( 8 ) derivatives.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…The presence of this interaction is able to stabilize the geometry of a molecule as well as to change the electron density distribution and further molecular features. The current work is a continuation of our study on N -oxide type compounds on the basis of diverse theoretical approaches. We have studied previously picolinic acid N -oxide as a small system, nevertheless with complicated spectroscopic features and proton dynamics. Static models were not able to reproduce its features, and the use of Car–Parrinello molecular dynamics enabled us to obtain an accurate picture of the bridged proton delocalization.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we focused on intra- and intermolecular interactions in two N -oxides: 2-(N,N-dimethylamino-N-oxymethyl)-4,6-dimethylphenyl ( 1 ) [ 43 ] and 5,5’-dibromo-3-diethylaminomethyl-2,2’-biphenol N -oxide ( 2 ) [ 44 ]. N -oxides are interesting objects for experimental and theoretical studies because of their unusual chemical structure, possessing N→O bonds, which is involved in inter- or intramolecular hydrogen bond formation [ 45 , 46 , 47 , 48 , 49 ]. It was showed that the N -oxide group exhibits proton acceptor ability for hydroxyl, carboxyl, amine groups or water molecules.…”
Section: Introductionmentioning
confidence: 99%